2011
DOI: 10.1143/jpsj.80.023714
|View full text |Cite
|
Sign up to set email alerts
|

Phonon Dynamics and Multipolar Isomorphic Transition in β-Pyrochlore KOs2O6

Abstract: We investigate with a microscopic model anharmonic K-cation oscillation observed by neutron experiments in β-pyrochlore superconductor KOs2O6, which also shows a mysterious first-order structural transition at Tp=7.5 K. We have identified a set of microscopic model parameters that successfully reproduce the observed temperature dependence and the superconducting transition temperature. Considering changes in the parameters at Tp, we can explain puzzling experimental results about electron-phonon coupling and n… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
13
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 28 publications
5
13
0
Order By: Relevance
“…This may be the case with the osmates analogue, KOs2O6, for which zero-temperature calculations have revealed a highly anharmonic potential with a flat bottom. [37][38][39][40] …”
Section: B Novel Rattling K Dynamics and Thermal Conductivitymentioning
confidence: 99%
“…This may be the case with the osmates analogue, KOs2O6, for which zero-temperature calculations have revealed a highly anharmonic potential with a flat bottom. [37][38][39][40] …”
Section: B Novel Rattling K Dynamics and Thermal Conductivitymentioning
confidence: 99%
“…In this Section, we calculate the alkali-metal RMSDs for each pyrochlore at the three temperatures, 20 K, 100 K, and 300 K, and these values can be compared directly to the experimental data summarized by Hattori and Tsunetsugu [11]. We also calculate the potential of mean force (PMF) for the alkali metals at the different temperatures from the formula [39]:…”
Section: Root-mean-square Displacements (Rmsds) and Potential Of Meanmentioning
confidence: 99%
“…Hattori and Tsunetsugu have investigated a realistic model including three dimensional anharmonic phonons with tetrahedral symmetry and have confirmed that T c is strongly enhanced with increasing the third-order anharmonicity of the potential. 18,19 Chang et al have discussed the superconductivity by using the strong-coupling approach in the anharmonic phonon model including fourth-order terms. 20 The present authors have revealed the anharmonicity-controlled strong-coupling tendency for superconductivity induced by rattling from the analysis of the anharmonic Holstein model in the strongcoupling theory.…”
Section: Introductionmentioning
confidence: 99%